ANALISIS MONITORING ARUS DAN TEGANGAN PADA TARIF R1-TR MENGGUNAKAN MIKROKONTROLER ATMEGA 328 - Agus Pramono; Abdul Aziz; Youngky Rizky A.W (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
One of the benefits that greatly supports the role of microcontrollers is the implementation in the form of modules and control systems in the application of industrial technology. The voltage and current monitoring system aims to facilitate monitoring of the electrical installation network so that it can be known for its small size. The microcontroller as a processor unit will be integrated into sensors and electronic components that are used as input readers from sensors which will then be monitored both manually and digitally. For this purpose, a prototype media is made to monitor the voltage and current that can be monitored by the load used during normal load and peak load, this is due to avoiding the occurrence of overcurrent and overvoltage in an electrical installation, so that the load crossing load does not exceed the specified limit and can resulting in a fire in the electrical installation.